2012
DOI: 10.1159/000341238
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Effects of Melatonin on Brain Arginine Vasotocin Immunoreactivity in Green Treefrogs <b><i>(Hyla cinerea)</i></b>

Abstract: Arginine vasotocin (AVT) and its mammalian homologue, arginine vasopressin (AVP), regulate a variety of social and reproductive behaviors, often with complex species-, sex- and context-dependent effects. Despite extensive evidence documenting seasonal variation in brain AVT/AVP, relatively few studies have investigated the environmental and/or hormonal factors mediating these seasonal changes. In the present study, we investigated whether the pineal hormone melatonin alters brain AVT immunoreactivity in green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 93 publications
3
30
1
Order By: Relevance
“…Melatonin has been shown to interact with neuropeptide and steroid pathways in many vertebrates, including teleost fishes (Falcón et al, 2010;Maitra and Chattoraj, 2006), frogs (Lutterschmidt and Wilczynski, 2012) and birds (Chowdhury et al, 2010;Ubuka et al, 2005). Unlike nonapeptides and steroid hormones (Goodson and Bass, 2000a;Remage-Healey and Bass, 2004), pilot studies showed that acute melatonin injections did not rapidly (5-120 min) change the output of the midshipman vocal system under our testing conditions (N.Y.F., personal observations).…”
Section: Melatonin Regulation Of Vocal Excitabilitymentioning
confidence: 75%
“…Melatonin has been shown to interact with neuropeptide and steroid pathways in many vertebrates, including teleost fishes (Falcón et al, 2010;Maitra and Chattoraj, 2006), frogs (Lutterschmidt and Wilczynski, 2012) and birds (Chowdhury et al, 2010;Ubuka et al, 2005). Unlike nonapeptides and steroid hormones (Goodson and Bass, 2000a;Remage-Healey and Bass, 2004), pilot studies showed that acute melatonin injections did not rapidly (5-120 min) change the output of the midshipman vocal system under our testing conditions (N.Y.F., personal observations).…”
Section: Melatonin Regulation Of Vocal Excitabilitymentioning
confidence: 75%
“…Indeed, advances in understanding nonapeptide function and social behavior in the lab have been made in several examples of tractable, non-traditional species. These examples include meadow voles [38], mandarin voles [39], tuco tucos [40], deer mice [41, 42], African striped mice [43, 44], guinea pigs [45], tree shrews [46•], titi monkeys [47•], rhesus macaques [48, 49], zebra finches [50, 51], anole lizards [52], tree frogs [53], butterfly fish [54], and cichlid fishes [55, 56]. …”
Section: Reconsidering Model Organismsmentioning
confidence: 99%
“…These counting methods allowed us to retain more animals in the statistical analyses, in contrast to eliminating an animal if 2 or more consecutive sections were missing or damaged [e.g. Lutterschmidt and Wilczynski, 2012]. The mean number of missing or damaged sections across all animals and regions was 1.42 (±0.03 SE).…”
Section: Immunoreactive Cell Countingmentioning
confidence: 99%